Current trends in the management of glioblastoma in a French University Hospital and associated direct costs. (8th January 2016) - Henaine, A. M.; Paubel, N.; Ducray, F.; Diebold, G.; Frappaz, D.; Guyotat, J.; Cartalat‐Carel, S.; Aulagner, G.; Hartmann, D.; Honnorat, J.; Armoiry, X.
Summary: What is new and objectives: Trends in the care of glioblastoma in actual practice settings are poorly described. In a previous pharmacoepidemiologic study, we highlighted changes in the management of patients with glioblastoma (GBM) newly diagnosed between 2004 and 2008. Our aim was to complete and to extend the previous report with a study of a cohort of patients diagnosed in 2011 to emphasize the trends in the pharmacotherapy of GBM over the last decade. Methods: A single‐centre study was undertaken of three historic cohorts of GBM patients newly diagnosed during years 2004, 2008 and 2011 (corresponding to groups 1, 2 and 3, respectively) but limited to patients eligible for radiotherapy after initial diagnosis. The type of medical management was described and compared, as well as overall survival and total cost from diagnosis to death or the last follow‐up date. Cost analysis was performed from the French sickness fund perspective using tariffs from 2014. Results: Two hundred and seventeen patients (49 in Group 1, 73 in Group 2, 95 in Group 3) were selected with similar baseline characteristics. Fluorescence‐guided surgery using 5‐ALA was increasingly used over the three periods. There was a strong trend towards broader use of temozolomide radiochemotherapy (39%, 73% and 83% of patients, respectively) as first‐line treatment as well as bevacizumab regimen at recurrence (6%, 48% and 58% of patients, respectively). The increase in overall survival between Group 2 and Group 1 was confirmed for patients in Group 3 (17·5 months vs. 10 months in Group 1). The mean total cost per patient was 53368 € in Group 1, 70 201 € in Group 2 and 78355 € in Group 3. Hospital care represented the largest expenditure (75%, 59% and 60% in groups 1, 2 and 3, respectively) followed by chemotherapy drug costs (11%, 30% and 29%, respectively). What is new and conclusion: This is the first study to report on changes in the management of GBM in real‐life practice. The ten‐year study indicates an improvement in overall survival but also an increase in total cost of care. The data should be useful for informing the care of GBM patients in settings similar to ours. Abstract : Figure 1 shows Kaplan Meier curves of overall survival for the three cohorts of patients and emphasizes the improvement of care over the last decade.